INFLUENCE OF A COMPLEX FEED ADDITIVE ON THE DIGESTIBILITY OF NUTRIENTS IN THE FATTENING OF KARAKUL SHEEP - Yahyayev Baxtiyor Sadullaevich (Scholar Express Journals, 2022)
The organization of full-fledged feeding is the main factor in the realization of the genetic potential of farm animals. In this regard, the use of effective feed additives in feeding animals can increase the energy and biological value of diets. This article presents the results of studying the effect of feed additives on the digestibility coefficients of nutrients in the stall fattening of Karakul sheep. In experiments on feeding sheep, feed additives were used in the complex: 1) bentonite as a source of minerals; 2) probiotic "Baktovit" for fodder purposes as a natural biostimulant; 3) carbamide as a source of nitrogen and increasing the protein nutritional value of diets for ruminants, 4) chlorella algae suspension as a source of biologically active substances.
Keywords: Karakul sheep; probiotic; carbamide; bentonite